Assay Of Rifampicin In Pharmaceutical Formulation: Comparison Of Spectrophotometric And Microbiological Methods - SARBJIT SINGH JHAMB; RAMAN PREET SINGH (International Journal of Pharma and Bio Sciences, 2010)
Micrococcus luteus was employed for the assay of rifampicin in fixed-dose combinations (FDCs) of anti-tubercular drugs containing rifampicin, isoniazid, pyrazinamide and ethambutal. The microbiological assay was compared with spectrophotometric assay for estimation of rifampicin in the FDCs as well as in dissolution studies of the FDCs. The microbiological method was found to be more sensitive and accurate as compared to spectrophotometric assay and did not show any interference in the presence of other anti-tubercular drugs. The limits of detection and quantification for microbiological method were 0.1 µg/ml and 0.64 µg/ml, respectively.